Gender equality and sustainable development - Leach, Melissa, ed (Routledge, 2016)
Gender Equality and Sustainable Development calls for policies, investments and initiatives in sustainable development that recognize women’s knowledge, agency and decision-making as fundamental. Four key sets of issues - work and industrial production; population and reproduction; food and agriculture, and water, sanitation and energy provide focal lenses through which these challenges are considered. Perspectives from new feminist political ecology and economy are integrated, alongside issues of rights, relations and power. The book untangles the complex interactions between different dimensions of gender relations and of sustainability, and explores how policy and activism can build synergies between them. Finally, this book demonstrates how plural pathways are possible; underpinned by different narratives about gender and sustainability, and how the choices between these are ultimately political.